PERKEMBANGAN ANAK SUKU MADURA - Dhonna Anggreni; Rahmi Syarifatun Abidah (Hospital Majapahit (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT MOJOKERTO), 2015)
Madurese ethnic migrant families often pay little attention to the health and even the majority have children in large numbers so that child development is often not considered. Development (development) is increasing ability (skill) in the structure and function of the body is more complex in a regular pattern and can be predicted, as a result of the maturation process. The purpose of this study is to monitor the development of pre-school children, social mental Madura tribe migrants in Surabaya. This research was conducted qualitatively in the Madura tribe all mothers who wander in the Village Simolawang Simokerto Surabaya who have children under 5 years of age. Each respondent conducted interviews and observation for 2 days. The number of mothers in the period of November 2013 as many as 37 people. The total of all respondents conducted interviews and observations. The results of the study explained that most children in the village Simolawang not impaired in mental development of social (75.7%), only a small fraction impaired (24.3%).